Palynology of a lower Wenlock (Silurian) shelf-basin transect, Wales and the Welsh Borderland - Swire, Paul Henry (1991)
Well-exposed lower Wenlock sections and borehole sequences, representing various facies along a shelf-basin transect in Wales and the Welsh Borderland, have been sampled for palynomorphs. Primary attention is paid to the type area in Shropshire, including stratotypes of both lower and upper boundaries of the Sheinwoodian Stage, with sampling as close as 10cm through the boundary horizons. The study has been extended into other sequences on the shelf to nearshore facies in the Bristol area and to basinal sections in North Wales.